The Role of Work Motivation Mediation in the Relationship Between Workload and Performance at Puskesmas in Tanjung Palas District, Bulungan Regency - Awing Lidiya Lian; Erick Karunia; Syahran Syahran; Budi Hasyim; Aswan Aswan (Jurnal Economic Resource, 2026)
This study examines the effect of workload on employee performance, with work motivation as a mediating variable, among employees at Antutan and Tanjung Palas Health Centers in North Kalimantan, Indonesia. A quantitative explanatory research design using a cross-sectional survey and SEM-PLS analysis was employed, with 136 respondents. Results show that workload does not significantly affect work motivation or performance, whereas work motivation significantly and positively influences performance. Moreover, work motivation fully mediates the relationship between workload and performance. The study highlights the critical role of motivation in sustaining employee performance, suggesting that organizational strategies should prioritize motivational interventions over workload reduction.